PENERAPAN METODE FIELD TRIP TERHADAP KEMAMPUAN MENULIS PUISI PADA SISWA KELAS IV SDN 13 NANGA PINOH - Sari, Wulan; Wibowo, Deki; Mutaqim, Nur Sulistiyo (STKIP Melawi, 2023)
This study aims to determine the ability to write poetry in class IV students of SDN 13 Nanga Pinoh before and after the field trip method is applied. The research was conducted based on the background of the problem of students' lack of interest in writing poetry. Through this research, students are expected to be able to express their ideas, thoughts, and feelings in the form of poetry. This study used the field trip method for fourth grade students at SDN 13 Nanga Pinoh. This type of research is an experiment using the Design One-Group Pretest-Posttest form. The population in this study were fourth grade students at SDN 13 Nanga Pinoh using a total sampling technique or saturated sample totaling 28 students consisting of 15 male students and 13 female students. The results of this study obtained an average score of 57.32 pretest and 83.57 posttest. Based on the results of hypothesis testing using the field trip method the ability to write poetry improves the learning outcomes of Indonesian language students in grade IV SDN 13 Nanga Pinoh, the value of Â = 12.36 and = 0.374 is obtained so that Ho is accepted. So it can be concluded that there is a significant difference in students' writing poetry before and after using the field trip method.